EMI troubleshooting cookbook for product designers - Andre, Patrick G.; Wyatt, Kenneth (Product development engineer) (Edison, NJ SciTech Publishing Inc., 2014)
We present methods that require only a basic understanding of electromagnetic theory and minimal EMI/EMC background. Our goal is to offer the user ideas derived from our experience so that engineers and technicians can develop their own personal troubleshooting idea, method, or diagnostic tool. Thus we provide guidelines on how to approach an EMI failure, things to try, and then how to choose the right parts and balance cost, performance, and schedule. We hope the book will make this phase of product design less stressful.
Electronic reproduction.
Keywords: Electromagnetic interference; Electromagnetic compatibility; Shielding (Electricity) -- Standards; Electromagnetic fields; Electromagnetic theory; Product design; Electronic books